The Impact of Naturalistic Age Stereotype Activation - Strickland-Hughes, Carla M.; West, Robin L. (Frontiers in Psychology, 2021)
Almost self-fulfilling, commonly-held negative stereotypes about old age and memory can impair older adults’ episodic memory performance, due to age-based stereotype threat or self-stereotyping effects. Research studies demonstrating detrimental impacts of age stereotypes on memory performance are generally conducted in research laboratories or medical settings, which often underestimate memory abilities of older adults. To better understand the “real world” impact of negative age and memory stereotypes on episodic memory, the present research tested story recall performance of late middle-aged and older adults (N=51) following a naturalistic age stereotype manipulation, wherein every day, newspaper-style materials (comics and puzzles) were either embedded with negative age and memory stereotype stimuli (stereotype group) or neutral stimuli (control group). Furthermore, all participants were tested in favorable, familiar environments. Potential moderators of the stereotype effects, e.g., metamemory beliefs, were assessed at baseline. Current memory evaluation and subjective age, as well as perceived stereotype threat and task-related anxiety, were assessed following the stereotype manipulation as potential mechanisms of the expected stereotype effects. Results suggested a contrast effect, as the stereotype group demonstrated superior story recall performance compared to the control group. Marginally significant moderation effects by age and perceived stereotype threat indicated that stereotype rejection was present for late middle-aged adults but not older adults, indicative of stereotype lift, and for individuals who reported low and average, but not high, levels of perceived stereotype threat. Additionally, a trend suggested more positive memory evaluation for those in the stereotype group who reported awareness of the stereotype stimuli than those who did not notice the stimuli. These results are consistent with other research demonstrating benefits to memory performance in adulthood based on motivational and contextual factors, such as using relevant memory materials and testing in favorable conditions. Moreover, the results of this study contribute to our understanding of individuals’ responses to different types of stereotype stimuli, and the differential impact of stereotype manipulations that are subtle versus blatant. Individuals were motivated to counteract negative stereotype effects when conditions were supportive, stereotype presentations were naturalistic, and personal beliefs were positive.